Institucionalização das práticas de controle interno em uma universidade pública: uma análise sob o enfoque da teoria institucional - Araújo, Sheila Alice Gajadhar (2021)
By managing public values, universities' internal controls play an important role in achieving institutional goals and objectives. To achieve effectiveness and achieve value addition, achievement of goals, among all other factors linked to a good internal control structure, it is important that it is institutionalized in the environment in which it operates, so the objective of this study is to analyze the process of institutionalization of internal control practices in a Public University. The research is classified as qualitative and descriptive. Interviews were carried out with the members of the Governance, Compliance and Integrity Committee (CONGOV) of the University under analysis. After conducting the interviews with the servers that make up CONGOV, a content analysis of the responses was carried out in order to collect the information which the research proposes. After that, analysis will be done using the Iramuteq® software. The main results indicate that the process of institutionalization of internal control practices predominantly identified was Habitualization and Legitimation. Habitualization reveals that internal control practices are in the process of modifying the environment. In turn, Legitimation makes the agents responsible for the institutionalization of practices use them as a legitimation tool for society, the federal government, ministries and internal agents themselves.